Algorithmic Reasoning: A Type of Imitative Reasoning in Solving Geometry Problems - Zhafira Ayu Prameswari; Indriati Nurul Hidayah; Tjang Daniel Chandra (Universitas Suryakancana, 2026)
This study aims to describe imitative reasoning of the algorithmic reasoning type among junior high school students in solving mathematics problems. Imitative reasoning is a way of thinking that follows procedures that have been taught without fully understanding the underlying concepts of the strategies. Meanwhile, algorithmic reasoning refers to imitative reasoning that relies on recalling strategies learned in previous lessons. This research employed a qualitative descriptive approach and was conducted with grade VIII students at one of the MTsN in Kediri City in the 2024/2025 academic year. Two subjects were selected based on test answer criteria that indicated the use of imitative procedures in problem-solving strategies that were frequently encountered, as well as imitation of strategies derived from information related to the questions. The results showed that the subjects did not fully understand the basic concepts underlying the selection of problem-solving strategies. They focused only on strategies that were familiar or had been learned previously. Interview results revealed that the two subjects had different bases for choosing strategies: S1 selected strategies based solely on those used in familiar problems, while S2 relied on surface information connected to the strategies they remembered. However, both subjects were unable to justify or prove the correctness of the strategies they chose.